DFT Studies on the Stereoselective Three-Component Ugi Reaction - Sharifzadeh, Elaheh Sadat; Shiraz, Nader Zabarjad (Orbital: The Electronic Journal of Chemistry, 2019)
studied theoretically based on DFT calculations. Structures of reagents, products, intermediates, and transition states were optimized at M062X/6-31+g(d,p) level of theory in gas phase and in methanol as a common solvent for this reaction. The reaction takes place through several processes, including atom inversion, bond rotation, acid-base, nucleophile-electrophile competitions. These diverse phenomena were studied to provide a clearer picture of the mechanism of this valuable reaction, especially in terms of stereochemistry considerations. According to the results, the enthalpy of the reaction was -45.9 and -41.2 kcal/mol for the dominant product in gas phase and in methanol. The stereoselectivity of the reaction was under the kinetic control of nucleophilic attack of isocyanide to less hindered si-face (Ea= 4.1 compared to 7.4 kcal/mol for re-face) of more stable chiral (E)-iminium in methanol. DOI: http://dx.doi.org/10.17807/orbital.v11i1.1214